Observation of recoil magnetization curves outside the major loop in Co, Fe, and Ni films - Geshev, Julian Penkov (2021)
We report a peculiar magnetization reversal observed in magnetron-sputtered Co, Fe, and Ni films. We found that some recoil (minor) magnetization curves lie entirely and way outside the major loop, a phenomenon referred to here as a recoil-curve overshoot. The greatly enhanced recoil curve’s remanence and coercivity result in an up to 2.5-fold increase of loop’s area. The model of pairs of exchange-coupled grains with misaligned anisotropy axes reproduces, in a very good agreement with the experiment, all key features of the recoil-curve overshoot as well as the kink that some major loops present before saturation. The disclosed features of the ferromagnetic hysteresis provide further insights into this important classical phenomenon.